ERROR ANALYSIS ON THE USE OF PREPOSITIONS IN STUDENTS’ WRITING OF THE TENTH GRADERS OF SMK N 2 KUDUS - Astuti, Vivi Dwi; Madjdi, Achmad Hilal; Kurniati, Diah (Universitas Muria Kudus, 2023)
The purpose of this study was to identify and classify types of errors in the use of prepositions in writing descriptive text by class X students of SMK Negeri 2 Kudus. Researchers analyzed errors using Dulay's theory, namely omission, addition, misformation, and misordering. Researchers used qualitative methods and documents for data collection. The document was in the form of descriptive text with different topics made by class X students of SMK Negeri 2 Kudus for the 2022/2023 academic year. Researchers took 5 students with a total of 15 texts. This research was conducted by performing an error analysis procedure. The first step was to collect samples from students to obtain information obtained through tests using prepositions of time, place, and direction on 5 students with a total of 15 texts. The second step was identifying the error. The third step explained the errors related to the forms of errors made by students. The next step was to describe the error and explain the cause of the error. The final stage was the evaluation of errors, where the errors made by students are evaluated. The results showed that the most errors were in misinformation with 19 errors and 86.4%. In the omission error, there was 1 error and 4.5%. The addition error was only 2 errors and 9.1%. And lastly, there were no errors made by students in Misordering.